THE EFFECT OF EDUCATIVE GAME TOOLS (PUZZLE FLANEL) ON THE EARNING ABILITY OF CHILDREN AT 4-5 YEARS AGE IN PAUD RENGGALI, EAST BEKASI, WEST JAVA - Mumum Mulyati (STIT AL-AMIN KREO TANGERANG, 2020)
Research on improving early numeracy process of children aged 4-5 at Early Childhood Education (ECE) programs in Renggali by using flannel puzzle, ice cream sticks, and buttons stucked on flannel media. Early numeracy isfundamental for understanding concept and meaning of numbers in order to solve daily logic problems of early-aged children. The games tools puzzles used in this study are made of flannel, dakron, and chlid-friendly duplex. Innovative flannel puzzles were created and used in order to stimulate the children’s learning so that fun learning method can be applied. An action research was employed in this study of which 15 students of ECE were selected as the subject. Data of the study was collected from a classroom action research design consisting of four steps: planning, action, observation, as well as reflection and was analyzed by means of descriptive, qualitative, and quantitative methods. Findings of the study reveal that student’s early numeracy skill can be seen frompercentage of children’s skill that was 44.66%prior to treatment and has increasedto 49.25% in the end of intervention. Findings show that the children’s skillis relatively high which isabout 90.16%as investigated in this study.